Synthetic MRI of prostate: correlation of T1 and T2-mapping with PI-RADS v2 scores - Corrias, Giuseppe; Sanna, Giorgia; Eusebi, Laura; Testini, Valentina; De Lisa, Antonello; Guglielmi, Giuseppe; Saba, Luca (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: There has been a drive to develop methods of quantitative Magnetic Resonance Imaging (MRI) imaging such as the calculation of T1 and T2 relaxation times and ADC values from diffusion-weighted imaging (DWI) to develop imaging biomarkers that complement subjective radiological assessment. This retrospective study aims to evaluate if T1 and T2 relaxation times are significant predictors of malignancy, correlating them with the PI-RADS v2 scores. Methods: This is a retrospective, monocentric, observational study, which included 33 consecutive patients with clinically significant prostatic cancer subjected to prostate MRI by regular clinical practice. We used T1 MP2RAGE and T2-multi-TE FSE 2D sequences with a reconstruction of T1 and T2 maps at the dedicated workstation. Lesions were identified by a radiologist who attributed the PI-RADSv2 score and then traced the Regions-of-Interest (ROI)also in the corresponding areas of healthy tissue. Wilcoxon signed-rank test in fixed ranks was used for comparison. Results: We found statistically significant differences between relaxation time of the tumor and healthy tissue of the peripheral zone (PZ) (T1maps: p=0.043) (T2maps: p=0.043), and the transition zone (TZ) (T1maps: p=0.018) (T2maps: p=0.062). The Spearman test shows a tendency to a correlation between relative PI-RADS scores and T2-times within the peripheral zone(p=0.060) and T1-times within the transition zone (p-value=0.053). Conclusions: There is a significant difference between the T1 and T2-relaxation times of pathological tissue and that of healthy prostate, both for lesions in the TZ as well as in the PZ. This reflects the intrinsic physical characteristics of the analyzed tissues represented as relaxation times of transverse and longitudinal magnetization. There is also a tendency to a correlation between PIRADS scores and T1/T2 relaxation times.